EMPLOYEE LOYALTY IN MANUFACTURING INDUSTRIES: EMPIRICAL FINDINGS FROM MALAYSIA - Zaherawati Zakaria; Nazni Noordin; Haidanazli Abdul Halim; Mohd Zool Hilmie Mohamed Sawal; Nurul Amira Azmi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study examines the factors that influence employee loyalty in the manufacturing industry in Malaysia. The goal of this study is to determine the extent of employee loyalty in Integris (M) Sdn Bhd, as well as to determine the relationship between superiority, reward and compensation, working environment, and peer cooperation, all of which are independent variables that may influence employee loyalty, which is the dependent variable. Integris Sdn Bhd’s total workforce is 300 people and the researchers used descriptive statistics and Pearson Correlation to analyze the findings, and the results show that there is a positive significant relationship between superior, reward and compensation, and working environment in terms of employee loyalty, but no such relationship exists between peer cooperation and employee loyalty. According to the study, employers, particularly in the manufacturing sector, should be more down to earth to foster excellent relationships and provide a platform for employees to express their thoughts. In future research, the study’s scope may be expanded, and new approaches may be used to obtain varied results that reflect employee loyalty.